PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA “MATH-U” BERBASIS APLIKASI ANDROID PADA SISWA KELAS XI DI SMAN 5 KOTA SERANG PADA MATERI LIMIT FUNGSI - Lia Gatra Hanafiani; Dewi Surani; Uswatun Khasanah; Ari Fidriyanto; Rohaeni Rohaeni (JURNAL EDUSCIENCE (JES), 2022)
AbstractOne of the impacts of the government's policy regarding PSBB during the COVID-19 pandemic is education that needs to be done from home or commonly called "Online Schools (on the network)". The process of teaching and learning activities that are usually carried out in the classroom, is now carried out through online platforms such as using Zoom Meeting, Google Meet, Google Classroom, WhatsApp Group and other platforms. As a result of online schooling, students experience a decrease in learning motivation and a decrease in understanding of mathematical concepts in learning. Therefore, the researchers created an android-based learning media called "Math-U". This study aims to: (1) develop an android application-based mathematics learning media and (2) determine the feasibility of the developed learning media. This study uses a four-D development model which consists of four stages, namely defining, designing, developing, and disseminating. The subjects of this study were students of class XI MIPA 1 SMAN 5 Serang City. Data were collected by observation, interviews and filling out questionnaires. The media feasibility data was analyzed with conversion references from experts. The results of the study are as follows: 1) the learning media developed consists of several menus, namely learning objectives, pre-test, function limits, post-test and profile (2) the feasibility of learning media appears based on the results of material expert validation with a score of 4.27 (very feasible) and the results of media expert validation with a score of 3.75 (adequate). This means that the learning media developed is suitable and adequate to be applied in learning mathematics. Keywords: Development, Learning Media, Math-U. AbstrakSalah satu dampak dari kebijakan pemerintah mengenai PSBB pada masa pandemi COVID-19 ini ialah pendidikan yang perlu dilakukan dari rumah atau yang biasa disebut “Sekolah Daring (dalam jaringan)”. Proses kegiatan belajar mengajar yang biasanya dilakukan di dalam ruang kelas, kini dilakukan melalui platform online seperti menggunakan Zoom Meeting, Google Meet, Google Classroom, WhatsApp Group dan platform lainnya. Akibat sekolah daring, siswa mengalami penurunan motivasi belajar dan penurunan pemahaman konsep matematis dalam pembelajaran. Oleh sebab itu peneliti membuat media pembelajaran berbasis android bernama “Math-U”. Penelitian ini bertujuan untuk: (1) mengembangkan media pembelajaran matematika berbasis aplikasi android dan (2) mengetahui kelayakan media pembelajaran yang dikembangkan. Penelitian ini menggunakan model pengembangan four-D yang terdiri atas empat tahap yaitu pendefinisian (define), perancangan (design), pengembangan (develop), dan penyebarluasan (dissemination). Subjek penelitian ini adalah siswa kelas XI MIPA 1 SMAN 5 Kota Serang. Data dikumpulkan dengan observasi, wawancara dan pengisian kuesioner. Data kelayakan media dianalisis dengan acuan konversi dari ahli. Hasil penelitian adalah sebagai berikut: 1) media pembelajaran yang dikembangkan terdiri atas beberapa menu, yaitu tujuan pembelajaran, pre-test, limit fungsi, post-test dan profil (2) kelayakan media pembelajaran nampak berdasarkan hasil validasi ahli materi dengan skor 4,27 (sangat layak) dan hasil validasi ahli media dengan skor 3,75 (layak). Hal ini berarti media pembelajaran yang dikembangkan sesuai dan layak untuk diimplementasikan dalam pembelajaran matematika. Kata Kunci: Pengembangan, Media Pembelajaran, Math-U.